Prevalence of cannabis use among tobacco smokers: a systematic review protocol. Issue 5 (2nd May 2022) - Skelton, Eliza; Rich, Jane; Handley, Tonelle; Bonevski, Billie
Abstract : Introduction: Understanding the prevalence of cannabis use among tobacco smokers has important implications for research in terms of intervention effectiveness and measurement in smoking cessation trials. The co-use of these substances also has important implications for health service planning, specifically ensuring appropriate and adequate clinical treatment. To date, there have been no synthesis of the literature on the prevalence of tobacco and cannabis co-use in adult clinical populations. Improved understanding of the current prevalence, route of administration and specific subpopulations with the highest rates of tobacco and cannabis co-use will support future intervention development. We aim to provide a pooled estimate of the percentage of smokers who report using cannabis and to examine the prevalence of co-use by sociodemographic characteristics. Methods and analysis: We will conduct a systematic review using six scientific databases with published articles from 2000 to 2022 inclusive (CENTRAL, CINAHL, EMBASE, Medline, PsycINFO, Psychology and Behavioural Sciences Collection, Scopus). Peer-reviewed journal articles published in English that report on tobacco and cannabis use will be included. Rates of co-use (simultaneous or sequentially) and routes of administration will be assessed. Use in populations groups will be described. Quality assessments will be conducted for all included studies. Data will be synthesised using a narrative approach. This study will be conducted from June 2022 to the end of August 2022. Ethics and dissemination: This review is based on previously published data and, therefore, ethical approval or written informed consent will not be required. It is the intention of the research team to disseminate the results of the systematic review as a peer-reviewed publication and conference presentations. PROSPERO registration number: CRD42020194051.